2016
DOI: 10.1111/jam.13215
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antiadhesive and antibiofilm activity of an ethanolic, anthocyanin-rich blueberry extract purified by solid phase extraction

Abstract: The overall study demonstrates the potential of anthocyanin extracts as natural effective alternative antimicrobial agents. Additionally, the extract's capacity to reduce adhesion without reducing bacterial growth reduces the likeliness of resistance development while reducing the probability of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 24 publications
6
57
1
1
Order By: Relevance
“…These results, which stand in line with those published in an earlier work regarding the effect of a blueberry extract upon S. aureus virulence factors, indicate that these blueberry extracts, even when present at concentrations bellow in which they are unable to inhibit bacterial growth they may still affect their metabolism in an advantageous way (Silva et al 2015). Moreover, some authors have reported that blueberry extracts may be effective in reducing biofilm formation, bacterial resistance structures notorious for their imperviousness to traditional antimicrobial agents (Zimmer et al 2014;Bjarnsholt 2013;Bridier et al 2015;Fux et al 2005;Silva et al 2016). However, it is important to note that the use of blueberry extracts to aid in the treatment of infections is, so far, an unlikely possibility, even if phenolic compounds have been hypothesized as interesting antibiotic coadjuvants (Alves et al 2014).…”
Section: Properties Referencesupporting
confidence: 84%
“…These results, which stand in line with those published in an earlier work regarding the effect of a blueberry extract upon S. aureus virulence factors, indicate that these blueberry extracts, even when present at concentrations bellow in which they are unable to inhibit bacterial growth they may still affect their metabolism in an advantageous way (Silva et al 2015). Moreover, some authors have reported that blueberry extracts may be effective in reducing biofilm formation, bacterial resistance structures notorious for their imperviousness to traditional antimicrobial agents (Zimmer et al 2014;Bjarnsholt 2013;Bridier et al 2015;Fux et al 2005;Silva et al 2016). However, it is important to note that the use of blueberry extracts to aid in the treatment of infections is, so far, an unlikely possibility, even if phenolic compounds have been hypothesized as interesting antibiotic coadjuvants (Alves et al 2014).…”
Section: Properties Referencesupporting
confidence: 84%
“…However, this effect was strain- specific and dose-dependent [ 53 , 88 ]. Blueberry extracts affected the growth of E. coli and P. aeruginosa , and they were able to significantly inhibit their biofilm formation and bacterial adhesion [ 50 ]—both important factors in their surface colonisation and infection [ 54 ]. Low concentrations of blueberry extracts proved to be more effective in inhibiting the biofilm formation, because a higher anthocyanin concentration could increase the production of exopolysaccharides in the presence of environmental stress, enhancing the protection of bacteria [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The role of anthocyanins from berries (mostly cranberries and blueberries) in UTI prevention and/or treatment still remains unclear. They interfere in vitro with the most prevalent and important virulence factor—the adhesion—of uropathogenic E. coli [ 46 , 50 , 58 ]. To the best of our knowledge, there are no in vivo studies relevant to the antibacterial activity of anthocyanins from blueberries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations